Economic cooperation despite of political conflict: Israeli traders' perception of Israeli-Palestinian food trade - Geesche M. Merkle; Rico Ihle; Yael Kachel; Ulf Liebe (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2013)
The ongoing political conflict between Israel and the Palestinian territories results in an increasing physical separation and societal alienation of both conflicting parties. In some contexts such as trade ongoing cooperation exists. We provide a micro-level analysis of economic interactions between Israeli and Palestinian wholesale traders of fruits and vegetables. We use a unique dataset gathered by a quantitative survey among Israeli wholesale traders in order to obtain evidence on their perspectives on this economic exchange. Trading patterns show vivid economic exchange of mainly informal character. Logistic regressions suggest that education and the personal social network play vital roles for the existence of Israeli-Palestinian trading relationships. Israeli traders feel not affected by the conflict but wish for its quick settlement. A low level of transaction problems is reported. They are mainly caused by the political and security situation and by the payment behavior of the Palestinian trading partners. Daily contacts of economic agents lead to continuous economic cooperation despite of ongoing political conflict and improve the perception of the actors of the other party.
Keywords: F14; Q17; Z13; 330; food trade; Middle East; quantitative survey; political conflict